Sliding Mode Control with Adaptive-Reaching-Law-Based Fault-Tolerant Control for AUV Sensors and Thrusters - Jiawen Li; Yujia Wang; Haiyan Li; Xing Liu; Zhengyu Chen (Journal of Marine Science and Engineering, 2023)
Ocean currents, mechanical collisions and electronic damage can cause faults in an autonomous underwater vehicle (AUV), including sensors and thrusters. For such problems, this paper designs a fault-tolerant controller that is independent of the results of the fault diagnosis. An adaptive reaching law is developed based on sliding mode control to shorten convergence times. For the chattering phenomenon, a weighted hyperbolic tangent function is adopted instead of the traditional sign function in sliding mode control. Simulations are carried out when thruster and sensor fail under the condition of ocean current disturbance, model uncertainty and sensor noise. Comparative simulation results show that the proposed method can accelerate the convergence speed of the state point and improve the trajectory tracking effect of the AUV. Consequently, the effectiveness of the proposed method is confirmed.